AN EXPLORATORY STUDY OF THE USAGE OF BANNED SOCIAL NETWORKING SITE ‘REDDIT’ IN INDONESIA - Moloney, Martin James; Sylva, Hanifah Mutiara (Universitas Prof. Dr. Moestopo (Beragama), 2019)
Reddit is a news aggregation website that uses user-sourced content to appeal to and incite interaction(s) with other ?Redditors? (Reddit users or contributors) within sometimes niche and often more generalized subjects. It is primarily a news aggregation website that acts as a forum for interested parties to join in discussion and contribute their own material relating to various topics. A voting process known as upvoting and downvoting moderates the posts and comments and dictates their popularity and exposure. Majority of its users to adopt virtual private networks (VPNs). Through mixed methods research, researcher seeks if its users directed abuse towards their own country, or people or revealed hidden interests in deviancy, sedition or dissent on the forum. The researchers studied the 200 most popular posts of all time on the r/Indonesia subreddit in February 2019. These were ranked by Reddit according to the number of upvotes/downvotes from readers of the forum. This research finds that the Indonesia sub-forum is not a concern to the country?s government and if anything the contributors are a benign meeting of oft-humorous, worldly and welcoming minds.